Análise da vulnerabilidade a inundações, na área urbana da microbacia do Segredo em Campo Grande – MS - Gomes, Adriane Fagundes Lino (2021)
Brazil is known for being a developing country and is more susceptible to natural impacts, due to the lack of control and mismanagement in the issue of land use and occupation, causing natural disasters such as flooding in urban areas. Substantially interfering with the environment, with the occupation of the soil through houses, paved roads, increasing the waterproofing index of this soil, resulting in the minimization of the practice of infiltration, thus reducing areas of rainfall contribution. In order to identify socio-environmental problems reconciling urban planning issues, this research aims to answer: “_What could be applied in practice to control actions against urban flooding?_”; Faced with this problem, the study aimed to understand how the interventions of the existing urban drainage master plan are managed, combining the type of correlated guidelines in relation to the vulnerability in relation to the infiltration areas of the Segredo Hydrographic Microbasin, the laws were carefully analyzed. and norms, mapping the compatible infiltration areas with the degree of development of the Municipality of Campo Grande - MS. The research resulted in 2 studies, the first using the bibliometric method, using the Scopus database from Elsevier, access provided by CAPES, with the application of the obtained data, analyzed using free-use software such as Mendeley and Vosviewer , the second chapter of this research was methodologically based on information from georeferenced data, with free use software applications QGis 3.6.16 Hannover in conjunction with Google Earth Pro. in a detailed and precise manner, in addition to identifying the main authors most cited in the Scopus database. There is a concern in the scientific community to help society through investigations into the risks of urban flooding, and even so, there are few publications in this area of interest based on the bibliometric method. An urban flood risk letter was generated, referring to the Segredo Microbasin in Campo Grande – MS. The methodologies that were presented are of great value, as they are easy to handle and both free of cost, enabling their application in areas where detailed information is lacking, as was the case in this research process. However, the product generated can be used by the government to help manage control measures for monitoring recurring problems with flooding in this urban area.